The Relationship between Gadget Addiction and Emotional Disturbance in Adolescents - Wraspati, Ni Komang Galuh Ayu; Sanjiwani, Anak Agung Sri Sanjiwani; Ni Ketut Ayu Mirayanti (Basic and Applied Nursing Research Journal, 2024)
Introduction: Adolescence is a transitional developmental period characterized by biological, cognitive, and socio-emotional changes. During this stage, adolescents are particularly vulnerable to emotional disturbances. In addition to depression and anxiety, these disturbances may include irritability, frustration, or excessive anger. One of the cur-rent phenomena contributing to adolescents' emotional challenges is gadget addiction. Frequent and excessive use of gadgets increases the risk of emotional and mental development issues in adolescents. The aim of this research is to investigate the relationship between gadget addiction and emotional disturbances in adolescents. Methods: This study employed quantitative descriptive research methods with a cross-sectional approach. The sample was selected using stratified ran-dom sampling techniques, resulting in 279 respondents. Data were ana-lyzed using the Spearman Rank Test. Results: The Spearman Rank Test analysis revealed a p-value of 0.000 (<0.05), indicating a significant re-lationship between gadget addiction and emotional disturbances in adolescents at SMA X Denpasar. The correlation coefficient value was 0.676, demonstrating a strong and positive relationship between gadg-et addiction and emotional disturbances. Among the five subscales of the questionnaire used in this study, most students showed emotional problems related to their learning experiences at school. Additionally, students exhibited symptoms such as restlessness, anxiety, irritability, and difficulty controlling their emotions. Conclusion: Adolescents are encouraged to use gadgets more responsibly and to balance their screen time with physical activities to mitigate emotional disturbances and promote overall well-being.